Turkish Cultural Policies in a Global World (Springer International Publishing, 2018)
This book provides a multidisciplinary analysis of the production of Turkish cultural policies in the context of globalization and of the circulation of knowledge and practices. Focusing on circulations, the book proposes an innovative approach to the transfer of cultural policies, considering them in terms of co-production and synchrony. This argument is developed through an examination of circulations at the international, national, and local levels; employing original empirical data and case study analyses. Divided into three parts the book first examines the Kemalist legacy, before turning to the cultural policies developed under the AKP's leadership, and concludes by investigating the production of cultural policies in the outlying regions of Turkey. The authors shed new light on the particular importance of culture to the understanding of the societal upheavals in contemporary Turkey. By considering exchanges as circulations rather than one-way impositions, this book also advances our understanding of how territories are (re)defined by culture and makes a significant contribution to the interrogation of the concept of "Westernization". This book brings into clear focus the reconfigurations currently taking place in Turkish cultural policy, demonstrating that while they are driven by the ruling party, they are also the work of civil society actors. It convincingly argues that an authoritarian turn need not necessarily spell the end of the cultural scene, and highlights the innovative adaptations and resistance strategies used in this context. This book will appeal to students and scholars of public policy, sociology and cultural studies.